2020
DOI: 10.1167/jov.20.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Limited interactions between space- and feature-based attention in visually sparse displays

Abstract: Top-down visual attention selectively filters sensory input so relevant information receives preferential processing. Feature-based attention (FBA) enhances the representation of relevant low-level features, whereas space-based attention (SBA) enhances information at relevant location(s). The present study investigates whether the unique influences of SBA and FBA combine to facilitate behavior in a perceptually demanding discrimination task. We first demonstrated that, independently, both color and location pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 71 publications
5
18
1
Order By: Relevance
“…Although this explanation may be compelling, on its own, the absent FBA effect we observed within accuracy and RT is equally consistent with both a dependent and an independent account of selective attention ( Liang & Scolari, 2020 ). This leaves us with the task of trying to determine why FBA enhancement effects were absent.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…Although this explanation may be compelling, on its own, the absent FBA effect we observed within accuracy and RT is equally consistent with both a dependent and an independent account of selective attention ( Liang & Scolari, 2020 ). This leaves us with the task of trying to determine why FBA enhancement effects were absent.…”
Section: Introductionsupporting
confidence: 73%
“…The goal of Experiment 1 was to modify the experimental design of Liang and Scolari (2020) Experiment 2 to elicit both SBA and FBA effects in a single task. Here, the location and color information indicated by an informative pre-cue each reflected at least one unique distractor (in addition to the target on valid trials), such that both cue types were necessary to completely isolate the target on wholly valid trials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that the suppressive effect is greatest when the two (spatially) adjacent targets are also close in feature space. However, we acknowledge that this topic is still a matter of debate [39][40][41][42] and further research is required to elucidate the nature of feature-based attention.…”
Section: Effects Of Feature-based Attention On Motion Direction Tunin...mentioning
confidence: 99%
“…The impact of spatial attention and FBA on the response modulations of visual cortical neurons have been investigated together in a number of studies [43]- [45]. Furthermore, psychophysical studies have confirmed the interaction between spatial and feature-based attention by analyzing spike activities from lateral the intraparietal [46], V4 [47], and MT [48] areas.…”
Section: Introductionmentioning
confidence: 99%